Are female headed households time poor? - Handa, Sudhanshu (International Food Policy Research Institute, 1998)
Female-headed Households (FHHs) in Jamaica are significantly poorer than Male-headed Households (MHHs) using per capita household consumption as a measure of welfare. It is often argued, however, that this measure overstates the welfare of FHHs because it ignores the consumption of leisure, and FHHs are thought to sacrifice leisure in order to raise consumption of good and services. Using the 1993 time use module of the Jamaican Survey of Living Conditions, a broad description of the time allocation patterns of members of male and female headed households is presented. A new measure of welfare is then developed that includes the consumption of leisure, and using this new measure, the relative disparity between male and female headed households remains unchanged, as does the ranking of individual households under alternative measures.